Path-Based Approach for Expanding Rail Transit Network in a Metropolitan Area - Li, Anjun; Wang, Dian; Peng, Qiyuan; Wang, Lisha (Journal of advanced transportation, 2022)
Rail transit network design is an important strategic problem in determining the layout of infrastructure and improving operating performance. A core transit network with multiclass rail transit systems has been constructed in many metropolitan areas worldwide. In this study, we aimed to expand an existing network to shorten travel time and improve service quality under the restriction of limited transport supply. We formulate the studied problem as a mixed-integer linear model to obtain optimal construction links, the number of trains required on each link, and the path selected by each traveler such that the weighted sum of total costs from the perspective of travelers, operators, and investors is minimized. The formulated model is path-based, where feasible paths for each traveler are generated to describe the full door-to-door journey, including the first/last mile, transfers, and multiclass transit modes. Owing to the complexity of the network design problem and because it is impractical to enumerate all feasible paths for each traveler in real-size problems, we propose a column generation-based algorithm to find both tight lower bounds and good-quality solutions efficiently by considering only a subset of feasible paths. We prove that the pricing subproblem in column generation can be decomposed into multiple shortest path problems, which can be solved efficiently and separately, based on O/D pairs instead of individual travelers. A rail transit network along a metropolitan corridor was studied as an example. Multiple computational experiments were conducted, and the results illustrate the validity and practicality of the proposed methodology for solving the problem.